Landschaftsarchäologie am DAI. Die Arbeiten der Jahre 2018 und 2019 - Rummel, Christoph; Schultze, Erdmute; Hohle, Isabel (e-Forschungsberichte des DAI, 2020)
Within the DAI, landscape archaeology is part of many scientific projects. The aim of the working group for landscape archaeology at the German Archaeological Institute (LAAD) is to provide a platform of exchange between these projects, in order to discuss different approaches and to communicate information about current and newly developing methods of investigation. In 2018 and 2019, two workshops addressed »landscape archaeology and exploitation of resources«. These included the presentation of the results of several DAI projects, as well as inspiring new impulses from projects dealing with this topic at the universities of Freiburg and Berlin, and the Excellence Cluster TOPOI in particular. Two more methodical workshops were focused on the usage of remote sensing data. Due to contacts with the DLR Earth Observation Center (EOC) in Oberpfaffenhofen, a particular focus lay on highlighting the possibilities of earth observation data, which are applied and tested in an existing cooperation project. The usage and possibilities of data generated by means of LIDAR-scans, UAVs and multi-spectral imaging were other main points of this discussion.